2022
DOI: 10.31219/osf.io/bv86n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tic prevalence by direct observation in an elementary school

Abstract: Introduction: Estimates of tic prevalence in community samples of children vary significantly. It is important to know the true prevalence of tics, as it aids in clinicians’ ability to counsel patients and families on the typical course of tics in those presenting for treatment. In this study, we directly observe elementary school children in the classroom setting in order to determine the prevalence of tics in the general school population.Methods: Participants were 215 children in kindergarten through fifth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Third, they diagnosed tics based on reports from parents and teachers-with careful questioning by trained research staff-but only supplemented by direct examination at the research visits if tics were reported to be "moderate," "severe," or "Tourette-like." We know from our recent New Tics study and previous research that many tics not recognized by parents or teachers are identified when the child is observed by clinicians or trained research staff [4]. For all these reasons, probably even more children with ADHD had tics than the 43% reported by Law and Schchar.…”
mentioning
confidence: 96%
“…Third, they diagnosed tics based on reports from parents and teachers-with careful questioning by trained research staff-but only supplemented by direct examination at the research visits if tics were reported to be "moderate," "severe," or "Tourette-like." We know from our recent New Tics study and previous research that many tics not recognized by parents or teachers are identified when the child is observed by clinicians or trained research staff [4]. For all these reasons, probably even more children with ADHD had tics than the 43% reported by Law and Schchar.…”
mentioning
confidence: 96%